Analisis Reaksi Pasar Terhadap Pengumuman Merger dan Akuisisi Pada Perusahaan Akuisitor yang Terdaftar di BEI - Adnyani, Ika Putri; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 23 No 3 (2018)DO - 10.24843/EJA.2018.v23.i03.p10, 2018)
This research is conducted on all acquisition companies that conduct acquisitions listed on Indonesia Stock Exchange 20 11 -2016 period. Sampling method using purposive sampling. The number of samples of this research is 50 companies. The market reaction in this study used abnormal return and trading volume activity . The t esting of information content will be done by looking at differences in cumulative abnormal return and the average trading volume of shares five days before and five days after the announcement of the acquisition. Data analysis technique used is paired sample t-test. Based on the test results, found there are significant differences in the abnormal return of the acquirer company before and after the announcement of the acquisition. However, there is no difference in trading volume activity of the acquirer's stock before and after the acquisition announcement   Keywords: acquisition s , stock market, abnormal return, trading volume activity